Prevalence and risk factors associated with common mental disorders among pregnant women in Kumasi, Ghana: a facility-based survey in selected primary care settings - Sandra Fremah Asare; Samuel Adjorlolo; Petra Brysiewicz (BMC Psychiatry)
Abstract Background Common mental disorders (CMDs) during pregnancy are linked to adverse maternal and neonatal outcomes, particularly in LMICs. However, risk factors for CMDs during pregnancy have received limited attention in preventive strategies. Therefore the study aimed to examine the prevalence and risk factors associated with common mental disorders among pregnant women in selected primary healthcare settings in Kumasi, Ghana. Methods A facility-based cross-sectional study was conducted among pregnant women in three selected public primary care facilities within Kumasi in the Ashanti Region of Ghana. A random sampling technique was used to select 232 pregnant women in their second and third trimesters who responded to the Self-Reported Questionnaire (SRQ-20). Descriptive and inferential analyses, including chi-square tests and firth logit regression models, were conducted using Stata (version 17) to identify the prevalence and factors associated with common mental disorders. Odds ratios were calculated with a 95% confidence interval to determine the association. Results This study found a CMD prevalence of 12.0% (95% CI: 8.3–16.9%) among the studied population. Overweight (adjusted Odds Ratio [aOR] = 0.17; 95% CI:0.03–0.96) and obese (aOR = 0.11; 95% CI:0.02–0.66) individuals exhibited a lower risk of CMD compared to those with normal BMI, while those with diabetes demonstrated a significantly increased risk (aOR = 8.59; 95% CI:1.41–52.24). Conclusion The significant link between diabetes and increased CMD risk underscores the necessity for comprehensive care strategies that address both physical and mental health needs concurrently by integrating care pathways into primary obstetrical care.